2019
DOI: 10.1177/1756287218818076
|View full text |Cite
|
Sign up to set email alerts
|

An update on the best approaches to prevent complications in penile prosthesis recipients

Abstract: Placement of inflatable penile prosthesis is a procedure frequently performed for medication-refractory erectile dysfunction. Device implantation is not without risks, and as the frequency of device implantation increases, so do associated complications. The aim of this work is to review the most frequent operative complications associated with implantation of inflatable penile prostheses, and to review the best approaches to prevent these most common complications. Complications can broadly be categorized as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 62 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…Both forms can require removal of the entire device. One of the most problems of the conservative treatments is the presence of the biofilm, which impedes antibiotic penetration and reduces phagocytosis [20, 21]. Once established which is the microorganism involved in the infection, an appropriate antibiotic therapy should be promptly performed (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both forms can require removal of the entire device. One of the most problems of the conservative treatments is the presence of the biofilm, which impedes antibiotic penetration and reduces phagocytosis [20, 21]. Once established which is the microorganism involved in the infection, an appropriate antibiotic therapy should be promptly performed (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Although technically harder, delayed re-implant surgery currently remains safer than immediate re-implant surgery. While newer salvage techniques have demonstrated increased success [21], further strong studies are required to identify how to improve techniques and strategies for immediate salvage procedures, enabling a complete exploitation of their benefits relative to delayed re-implantation, cost effectiveness, technically easier, and with a reduced risk of penis shortening.…”
Section: Resultsmentioning
confidence: 99%
“…Had prosthesis removal been elected, the options would include immediate reimplantation of a new device (termed “concomitant implant after explant”) or revision surgery at a later date. The challenge with delayed reimplantation is fibrosis of the canal and shortening of the penis but is considered safer for the patient [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because IPP implantation is an invasive treatment for ED patients, it might be associated with various complications, such as urinary retention, mechanical failure, and infection. 26 In this study, we also investigated the clinical outcome after implantation. The results showed that IPP implantation combined with sildenafil could increase the overall IPP survival rate and reduce the complication rate, swelling, and pain duration.…”
Section: Discussionmentioning
confidence: 99%